Qualidade do gasto público em educação para os municípios da região metropolitana de Natal-2007 - Silva, Veruska Pereira da (2011)
The aim of this thesis is to evaluate the quality of public spending on education for the municipalities of the Metropolitan Region of Natal (RMN) in 2009 by use of two theories: The Theory of Welfare (Welfare State) and the Public Choice Theory (TEP), both important to understand the relationship between education and economics. The study also uses principles of microeconomics and public sector economics to get a better idea of the role of education in economy and society. It describes the development of the educational policy in Brazil from 1988 to the Federal Constitution of 2010, following the major changes in basic education during each government. The characteristics of the RMN municipalities were illustrated with socioeconomic indicators, while educational indicators were used to characterize each municipality regarding education. The model used in this study was developed by Bertê, Brunet and Borges, the data was collected on the back of the School Census 2009 and the Brazil Exam 2009 and it was processed quantitavely in the Information System on Public Budgets in Education (SIOPE) by use of the statistical method called standardized score of the normal cumulative distribution function. The quality of public spending on education is the result of the relation between performance indicator ratio and expense ratio. For the qualitative analysis of results, the criteria of efficiency, efficacy and effectiveness were used. The study found that municipalities with higher expenses showed a worse quality of spending and failed to convert the expenditure incurred into performance, thus confirming ineffectiveness